2018
DOI: 10.1111/jocd.12797
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of oral tranexamic acid and Glycyrrhizin compound in the treatment of recalcitrant Riehl’s melanosis

Abstract: Summary Background Up till now, there is no standardized and satisfactory treatment strategy for Riehl’s melanosis. Objective In this pilot study, we evaluated the efficacy and safety of a novel combination therapy with oral administration of tranexamic acid (TA) and Glycyrrhizin compound for recalcitrant Riehl’s melanosis. Methods Ten patients with Riehl’s melanosis were recruited in this study. After elimination of potential contraindication, all patients were treated with 500 mg TA together with 150 mg Glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Instead, notable inflammatory infiltration and angiogenesis were identified. These results indicated vascular structures and inflammatory infiltrations could largely affect skin tones, coherent with recent clinical evidence that anti‐inflammatory and anti‐angiogenesis therapies could improve skin tones in patients with melasma 15 and melanosis 16 . It was worth noting that new microvessels were more evident on live images rather than captured ones, as the erythrocyte showing apparent movement could only be reflected by video.…”
Section: Discussionsupporting
confidence: 79%
“…Instead, notable inflammatory infiltration and angiogenesis were identified. These results indicated vascular structures and inflammatory infiltrations could largely affect skin tones, coherent with recent clinical evidence that anti‐inflammatory and anti‐angiogenesis therapies could improve skin tones in patients with melasma 15 and melanosis 16 . It was worth noting that new microvessels were more evident on live images rather than captured ones, as the erythrocyte showing apparent movement could only be reflected by video.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies have demonstrated good efficacy on treatment of Riehl's melanosis with low-pulse energy 1064-nm Q-switched Nd-YAG laser; combination of low-fluence Q-switched 1064 nm Nd-YAG laser, hydroquinone cream and oral tranexamic acid; and Q-switched 1064 nm Nd-YAG laser-operated as a dualpulse at half-fluence and 140-μs intervals in Asian skin [ Table 3 ]. [ 41 42 43 44 45 46 ] However, in our experience, the improvement offered by Q-switched ND-YAG laser is modest and short lasting.…”
Section: Treatment Of Acquired Macular Pigmentation Disordersmentioning
confidence: 67%
“…Both the glycyrrhizin compound and metronidazole have an anti-inflammatory effect. Due to the similar pharmacological efficacy to corticosteroids but with milder adverse effects (24), compound glycyrrhizin has been widely utilized in several dermatologic disorders for many years (6,8). Metronidazole is an antiprotozoal and imidazole-derived antibacterial agent; it also has immunomodulatory effects on leukocyte chemotaxis and suppresses cell-mediated immunity (25), which makes metronidazole an effective therapy option for FSD.…”
Section: Discussionmentioning
confidence: 99%